2016
DOI: 10.1007/s40744-016-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Use of Statins in Tocilizumab-Treated Patients with Rheumatoid Arthritis: A Post Hoc Analysis

Abstract: IntroductionPatients with rheumatoid arthritis (RA) have decreased survival because of increased cardiovascular risk compared with the general population, and treatment with tocilizumab (TCZ) has been shown to increase lipid levels; however, the relationship between lipids and cardiovascular risk is unknown. This post hoc analysis expanded on previously reported 24-week results by characterizing statin use and subsequent changes in lipid parameters in patients with RA treated with intravenous or subcutaneous T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
(32 reference statements)
0
17
0
3
Order By: Relevance
“…Multiple preclinical and clinical studies have analysed the impact of different statins on RA . Statins are given to patients with RA because of their increased risk for cardiovascular complications .…”
Section: Statins In Ramentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple preclinical and clinical studies have analysed the impact of different statins on RA . Statins are given to patients with RA because of their increased risk for cardiovascular complications .…”
Section: Statins In Ramentioning
confidence: 99%
“…A cohort study that included patients with a diagnosis of hyperlipidaemia who started statin intake showed that the connection between lowering low‐density lipoprotein cholesterol and cardiovascular events in RA was comparable to the association found in matched general controls . Another study analysed the effect of statins in patients treated for RA with tocilizumab . The rationale was that treatment with tocilizumab increases lipid levels.…”
Section: Statins In Ramentioning
confidence: 99%
See 3 more Smart Citations